The myth of transit: the making of a life by asylum seekers and refugees in Indonesia. Issue 7 (27th May 2016) - Sampson, Robyn C.; Gifford, Sandra M.; Taylor, Savitri
ABSTRACT: An increasing number of migrants are living in a state of indefinite 'transit'. In this paper, we report on interviews conducted in 2009 with 59 refugees and asylum seekers in Indonesia and describe how these individuals make a life despite their circumstances. While all participants were deeply affected by their position of uncertainty and insecurity, most sought to transcend these conditions and pursue significant life projects such as getting married, having children, becoming part of the local community, and working towards a better future. The current conceptualisation of transit as life in limbo does not wholly account for such permanent, life-changing experiences. We analyse the reasons why the use of the term 'transit' persists in international policy settings despite its incongruities, arguing that its ongoing political valence overrides its conceptual flaws.